Analysis of F− removal from aqueous solutions using MgO. (October 2018) - Kameda, Tomohito; Yamamoto, Yusuke; Kumagai, Shogo; Yoshioka, Toshiaki
Abstract: MgO was found to take up F − from NaF aqueous solutions due to the electrostatic attractive force between the positively charged MgO and F − . The F − adsorption by MgO can be represented by pseudo first-order reaction kinetics, and the magnitude of the apparent activation energy (71.6 kJ mol −1 ) confirms that this is a chemisorption process. The thermodynamic behavior of this process follows Langmuir-type adsorption, with the maximum adsorption amount of 5.6 mmol g –1 . The F − can be desorbed from MgO using NaOH solution. The regenerated MgO can still take up F − from the solution despite the lowered adsorption capacity. Therefore, it is possible to recycle the MgO for F − adsorption.